Dominant Negative TRAF3 Variant With Recurrent Mycobacterium abscessus Infection and Bronchiectasis. (3rd August 2022) - Liew, Mei Fong; Lim, Hui Fang; Liang, Mui Cheng; Lim, Ives; Tan, Zhaohong; Tan, Rachel Ying Min; Sam, Qi Hui; Soe, Win Mar; Tay, Sen Hee; Xu, Shengli; Chang, Matthew Wook; Foo, Roger; et al.
Abstract: Host factors leading to pulmonary nontuberculous mycobacteria (PNTM) disease are poorly understood compared with disseminated NTM disease, which is linked to the interleukin 12–interferon gamma signaling pathway. We investigated the tumor necrosis factor receptor associated factor 3 (TRAF3) R338W variant in a patient with recurrent PNTM infection, demonstrating TRAF3- and TNF-α-deficient phenotypes via ex vivo immune and cloning-transfection cellular studies.